Policy analysis of nutrition stewardship for prevention and control of Non-communicable diseases in Iran - Mohammad Amerzadeh; Amirhossein Takian; Hamed Pouraram; Ali Akbari Sari; Afshin Ostovar (BMC, 2023)
Abstract Background Non- communicable diseases (NCDs) are the main cause of death, which lead to over 73% of death and 62% of DALYs globally. As an unhealthy diet is the leading behavioral risk factor of NCDs, in line with the national action plan for the prevention and control of NCD, this study explored the nutrition-related stewardship problems to reduce the burden of NCDs in Iran. Methods This is a qualitative study. We interviewed 30 purposefully identified key informants, i.e., stakeholders, policymakers, and academics, from December 2018 to August 2019. All interviews were recorded and transcribed verbatim. We analyzed data using qualitative content analysis facilitated by MAXQDA 11 software. Results Ample policies and laws were identified, most of which were not or partially implemented. Despite some plausible efforts, NCDs do not seem to be a top priority for high-level managers and decision-makers. Besides, the role of non-state actors, i.e., the private sector, is marginal in NCD's planning and management. Whereas the government, e.g., the Food and Drug Organization (FDO), is the biggest player. Worse still, many harmful products are advertised and easily distributed across the country. Conclusion Iran's government has created a noticeable roadmap to battle NCDs despite imposing many sanctions and related socioeconomic problems. Nevertheless, more interventions are needed to strengthen the stewardship of NCDs by various stakeholders. We recommend the government to monitor the implementation of policies and advertisement of harmful products to prioritize prevention and control of NCDs. In addition, we advocate employing the capacity of non-state actors to reduce the consumption of unhealthy food and the burden of NCDs across the country, ultimately.